Poverty Alleviation through Sociocultural Education Programs to Improve The Social Welfare of The Community - Farouq, Mgs. Muhammad; Kriyantono, Rachmat; Hakim, Muhammad Lukman; Sahiruddin, S (Proceedings International Conference on Education Innovation and Social Science, 2024)
Poverty is still widely found in Indonesia, especially in rural areas. The relatively low level of education of rural communities results in a lack of community contribution to pursue welfare. There are still many rural people who do not have jobs in the area where they live. On the other hand, some regions in Indonesia are very advanced and developed which are not far from the countryside. This is a phenomenon that is quite concerning. This study examines the impact of the "Eco-Friendly Entrepreneurship for Youth and Adults" program implemented in Lembang, West Java, Indonesia, by PP PAUDNI Regional I Bandung and Jayagiri Center. The program aims to improve the social welfare of the community through eco-friendly entrepreneurship education for youth and adults. The research method used is descriptive qualitative with a case study approach. Data were collected through interviews, documentation, and observations with key informants, including the Head of PP PAUDNI Bandung, program participants from the Lembang community. The results show that the program successfully enhanced participants' economic well-being, preserved local culture, and protected the environment. Participants acquired sufficient entrepreneurial skills to start and develop businesses. This study concludes that non-formal education based on eco-friendly entrepreneurship has great potential in alleviating poverty and improving social welfare. Additionally, the goals of Education for Sustainable Development (ESD), which include developing the knowledge, skills, attitudes, and values needed to build a sustainable future, are reflected in this program, where participants are taught to balance economic growth, environmental preservation, and social welfare.